Delayed presentation of oral cancer: a case report / Alan Basil Peter ... [et al.] - Peter, Alan Basil; Abd Malek, Khasnur; Mohd Kornain, Noor Kaslina; Mohamad Ali, Norliana Dalila (Faculty of Medicine, 2023)
Non-healing, persistent mouth ulcer is a risk for cancer. At an early stage, oral cancer is usually painless and may lead to delayed diagnosis. Herein we describe an adult, with a chronic nonhealing tongue ulcer, who presented to a dentist and multiple general practitioners (GPs) and had a delayed appointment to see the tertiary healthcare centre for a diagnostic work-up. The patient's lack of awareness of his oral ulcer's risk and his condition's urgency further added to the delay. The delay in the diagnostic work-up could be improved by having an organized welldefined effective pathway to confirm or disprove the suspicion of cancer. Initial radiological imaging indicated a localized mass with no distant metastasis, and pathological findings confirmed squamous cell carcinoma. The patient underwent a partial glossectomy followed by chemotherapy and radiotherapy. Unfortunately, cancer progressed and advanced to stage 4, and the patient succumbed to cancer complications one year after the initiation of treatment. This article aims to create awareness among primary healthcare professionals to recognize the potential benefits of early intervention, thus minimizing unfortunate late presentation instances.